Roots and Tubers: An Alternate Energy Rich Feed Ingredients for Rural Pig Production - Osti, Netra Prasad; Mandal, Pulkit (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Pigs are neglected domestic animal species reared under poor care and management. Chwanche, Hurra and Bampudke are major native pigs of Nepal whereas Landrace, Yarkshire, Pakhribash Black, Tamworth and Durock are the introduced pigs. A survey was conducted in selected districts of Nepal in order to understand feeding system of indigenous pigs and also collect feed samples for chemical analysis. In all surveyed sites, the pig herd size was relatively small (2-4/farm). Kitchen waste from home or hotel, local seasonal vegetable or fruit i.e. non-consumable for human being, local sweet potato and their vines (in few areas), roots and tubers and their leaves such as- Pindalu (Clocasea sps), Sweet potato (Ipomoea batatus L), Turnip (Brassia rape) and Radish (Raphnes sativa L), rice bran and maize flour were the major feed ingredients. Sweet potato had high energy content as compared to other roots and tubers and was comparable to rice bran and maize which are the major sources of energy in livestock feeds. Findings thus indicated that roots and tubers in rural areas could be an alternative as of energy rich feed ingredients which could be utilized if maize and rice bran are expensive and unavailable. Further research on level of feeding, conservation technique and varietals improvement is needed. DOI: http://dx.doi.org/10.3126/hn.v11i1.7202 Hydro Nepal Special Issue: Conference Proceedings 2012 pp.42-43